Analisis Stabilitas Bendung Kalukku Kabupaten Mamuju - GoldyAwan J. Moily; Burhanuddin Badrun; Andi Rumpang Yusuf (Program Studi Teknik Sipil Universitas Bosowa, 2026)
A weir is a water structure with equipment built across a river. Weirs are designed to meet stability requirements, to guarantee the service life of the weir and its ability to raise the water level. Weir stability consists of stability against overturning, stability against soil bearing capacity, stability against shear forces, and eccentricity of loading. The problem formulation is the security value of the stability of the Kalukku Bnedung under normal conditions and river flooding. The aim of this research is an analytical study of the safety value of the Kalukku Dam under normal conditions and river flooding. The research method uses a survei method through literature study, collecting primary data, secondary data, rainfall analysis, and measuring weir stability. The dimensions of the Kalukku weir are 105 meters wide and the overall width of the weir is 111 meters. The research results show that stability against overturning (sf = 4.20 > 1.5) is safe, stability against sliding (sf = 1.99 > 1.50) is safe, the eccentricity of the load that occurs (e = 0.79 m < 4.21 m), the bearing capacity of the soil or the soil stress that occurs (omax = 22.61 tons/m2 > 1.37 t/m2), (omin = 10.28 tons/m2 > 0.63 t/m2). Stability value in flood water conditions, stability against overturning (sf = 3.9 > 1.25) which is safe, stability against sliding (sf = 1.50 > 1.2) which is safe, eccentricity of the load that occurs (e = 0.87 m < 2.10 m), soil bearing capacity or the soil tension that occurs (omax=13.56 tons/m2 > 1.41 t/m2), (omin= 5.61 tons/m2 > 0.59 t/m2).